Anatomy of a Crash-Test Dummy. - Guizzo, E. (IEEE spectrum)
Denton ATD, with facilities in Michigan and Ohio, manufactures some of today's most advanced crash-test dummies. The author relates his experience in visiting the company's facility in Milan, Ohio and discusses the detail of Hybrid III, a crash-test dummy model.